Analisis Kerentanan Fisik Abrasi Pada Pulau Derawan, Kabupaten Berau - Andrean Julianto Iryanto; Nadia Almira Jordan (Arsitektur Universitas Muhammadiyah Kendari, 2022)
Derawan Island is a cluster of islands that are connected to the Tourism Area of the Derawan and Maratua Islands, East Kalimantan Province. This Island experienced a threat of abrasion which compared to data in 2007, the area of Derawan Island in 2020 shrank by 12.60 ha, while in 2018 there was a deterioration of the coastline as far as 15 meters. This has an impact on changing landscapes and damage to buildings in coastal areas, as well as social and economic activities. This research was done to discover the rate of physical vulnerability to treat the negative impact of abrasion. This research used the Spatial Multi-Criteria Analysis method, including weighting on variables and performing Weighted Overlays by reviewing the level of physical vulnerability caused by abrasion on Derawan Island. The results of this study were the Derawan Island Area experienced moderate abrasion levels of 51% (6.33 Ha), whereas the area experienced high abrasion susceptibility of 19% (6.22 Ha), which covered the northern part of the island.